The influence of Western culture on the Central Asian States’ and Kazakhstan’s science - Sanat Ainakulov; Mereke Tulekova; Nurzhamal Oshanova (Trans/Form/Ação)
The relevance of the study is due to the fact that the Central Asia’s culture is of great interest for modern sociological science as an object of study of intercultural interaction and as a multifaceted, complex, controversial, and dynamic phenomenon. The topic of the influence of Western culture and philosophy on the science of more Eastern regions, according to the authors, has been rather neglected. The purpose of the paper is to study the influence of Western culture on the Central Asian states and Kazakhstan’s science, including philosophical, historical and cultural direction. The comparative approach was used to study materials on the development of Western science and their distribution in the foreign countries’ cultures, as well as the analysis of these materials. As a result, a series of statements was deduced that confirms the influence of Western science on Kazakhstan’s and Central Asia’s countries’ science. It was concluded that democratic ideas, educational sentiments and revolutionary movements, in Russia, had a significant impact on Central Asia and Kazakhstan.